The fundamental of housing affordability and affordable houses: a review - Azmi, N. (CRC Press/Balkema, 2016)
A misconception between housing affordability and affordable housing in Malaysian housing policy led to the problems in the housing market. Thus, what is the dissimilarity between housing affordability and affordable house in the housing market? This paper attempts to review the fundamental of housing affordability and affordable housing. In the context of housing, the emphasis of housing affordability is placed on the household income in determining the house prices, whereas, affordable house emphasis on home prices, however, overlook the household incomes. This study is expected to provide a thorough understanding and knowledge about housing affordability and affordable housing.